2018
DOI: 10.1200/jop.18.00419
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Impact of Academic Cancer Network Development on Clinical Integration, Quality of Care, and Patient Satisfaction

Abstract: Purpose: Many US academic centers have acquired community practices to expand their clinical care and research footprint. The objective of this assessment was to determine whether the acquisition and integration of community oncology practices by Yale/Smilow Cancer Hospital improved outcomes in quality of care, disease team integration, clinical trial accrual, and patient satisfaction at network practice sites. Methods: We evaluated quality of care by testing the hypothesis that core Quality Oncology Practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…The calibration curves visually showed that the averaged predicted LOS probability of the models were consistent with the observed outcomes across different LOS risk groups from low to high. By demonstrating the utility of ML algorithms, we determined the impact of several variables, shown to be predictors of short-term outcomes in EOC patients [ 14 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The calibration curves visually showed that the averaged predicted LOS probability of the models were consistent with the observed outcomes across different LOS risk groups from low to high. By demonstrating the utility of ML algorithms, we determined the impact of several variables, shown to be predictors of short-term outcomes in EOC patients [ 14 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It procures a surrogate for the technical complexity of a procedure. Surgical complexity is associated with prolonged LOS even with an established ERAS pathway in place [ 31 ]. Intrinsic non-modifiable predictors for LOS differ with operative complexity, and this should be considered when planning benchmarking and research across units.…”
Section: Discussionmentioning
confidence: 99%
“…It is clearly visible from these manuscripts that our field has evolved along the continuum from measurement to improvement. Several of the articles report evaluation of new models of care and provide some of the earliest information on the value of new models for early integration of palliative care, 2 creation of care networks, 3 and the oncology care model. 4 Others provide us with new approaches to quality measurement, 5 tools to assess barriers to quality improvement, 6 and pragmatic approaches to educate frontline providers on how to do quality improvement.…”
Section: Real-world Approaches To Quality Improvement In Oncologymentioning
confidence: 99%
“…5 Nowhere is this more evident than in oncology, where community health systems have begun to partner with academic medical centers, which are attempting to extend their reach into the community setting, where 85% of cancer care is delivered. 6,7 Several NCI-designated Comprehensive Cancer Centers have established partnership and affiliation models, including the Duke Cancer Network, 8 MD Anderson Cancer Network, 9 and Fox Chase Cancer Center Partners Program. 10 Although each network's relationship model is unique, these programs typically provide community hospital partners with access to consultative services, treatment protocols, research, and clinical trials.…”
Section: Introductionmentioning
confidence: 99%